Roles for RNA-binding proteins in development and disease - Brinegar, Amy E. (Brain Res, 2016)
RNA-binding protein activities are highly regulated through protein levels, intracellular localization, and post-translation modifications. During development, mRNA processing of specific gene sets is regulated through manipulation of functional RNA-binding protein activities. The impact of altered RNA-binding protein activities also affects human diseases in which there are either a gain-of-function or loss-of-function causes pathogenesis. We will discuss RNA-binding proteins and their normal developmental RNA metabolism and contrast how their function is disrupted in disease.